Online-Learning Effectiveness of Secondary Students - Chui, Hong Sheung; Hui, Wai Tin; Chui, Samuel Wing Ho (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This research study examines various factors that influence the effectiveness of online learning and students’ interest in applying technology in learning for secondary schools in Hong Kong. Confirmatory Factor Analysis confirmed the questionnaire developed for this study, demonstrating reliability and validity in measuring five factors: family support, students’ engagement, perceived online learning effectiveness, satisfaction with the online learning experience, and students’ interest in using technology in the future. Structural Equation Modeling was utilized to test the hypotheses. The findings confirmed that family support and students’ engagement have a positive effect on students’ perceived online-learning effectiveness, satisfaction with online learning, and interest in using technology in future studies. This research sheds light on the crucial effects of family support and students’ engagement on learning effectiveness and students’ satisfaction with online learning. Educators and policymakers can make informed decisions to optimize and enhance students’ online learning effectiveness, and apply these insights to future educational applications.